Pyogenic Granuloma in Kidney Transplant Recipient - Teixeira Cesar, Thiago Augusto (2023)
Objectives: This manuscript describes a clinical case of pyogenic granuloma with atypical presentation and evolution, and outlines a brief bibliographic review on the nosological entity. Introduction: Pyogenic granuloma is a common benign skin lesion, usually small, with some more common locations and predominance in females in adulthood. It has a correlation with trauma and medications. Its pathophysiology is in the initial stages of understanding. The typical histopathological alteration is a lobular arrangement of capillaries at the base. Treatment is surgical, with a low recurrence rate; there are non-surgical alternatives. Case report: We report a case of a 25-years-old renal transplant patient who develops a giant Pyogenic granuloma in the right forearm after a mild trauma, 2 years after transplantation from a deceased donor. He performs successive surgical excisions, with several recurrences, which disappeared only after discontinuation of tacrolimus and radiotherapy. The peculiarities of this case are: post-kidney transplant status, large size, recurrences after surgery and radiotherapy.. Conclusions: A patient with pyogenic granuloma, with atypical evolution, had a favorable outcome after identification and removal of a causative factor and alternative therapy. However, this report has limited potential for generalization. There are few publications of case series involving unusual situations, in addition do the involvement of the oral mucosa, paraungual/subungual regions and cases in pregnant women. Radiotherapy is a poorly performed intervention, which can be of value in refractory cases. Further studies are needed to achieve a greater understanding of this pathology and to describe treatment alternatives.